Comparison of the pre-emptive analgesia of low dose intravenous ketamine in combination with intravenous parecoxib versus intravenous ketamine alone on patients undergoing laparotomy under general anaesthesia - Ramli, Rabiatul Aida (2019)
Background: Pre-emptive analgesia is important for post-operative analgesia and reducing opioids requirement and their side effects after major surgery. The aim of this study is to compare the efficacy of low dose IV ketamine in combination with IV parecoxib versus IV ketamine alone as pre-emptive analgesia in patients undergoing laparotomy under general anaesthesia. Methods: A total of 48 patients, scheduled for laparotomy under general anaesthesia were randomised into two different groups of pre-emptive analgesia: Group R: low dose IV ketamine 0.3mg/kg in combination with IV parecoxib 40 mg (n= 24) and Group C: IV ketamine 0.3mg/kg alone in combination with placebo (normal saline) (n= 24) and administered before induction of anaesthesia. Both groups received standardized technique of general anaesthesia and post-operative analgesia using patient-controlled analgesia of morphine (PCAM). Both groups were assessed for dosage of rescue analgesia requirement at the recovery bay, pain intensity using visual analogue scale (VAS) over 24 hours, time for the first PCAM demand and total dose requirement of intra-operative and post-operative opioids. Results: Group R showed lower dose of rescue analgesia requirement at recovery bay [6.25 (16.9) vs 20.8 (28); p= 0.035], longer time for the first PCAM demand [70.8 (40) vs 22.2 (15.7); p< 0.001], less total requirement of PCAM within 24 hours post-operatively [-8.04 (4.6) vs -16.8 (6.46); p< 0.001] and less VAS at an hour and subsequently 4 hourly interval over 24 hours than Group C. Conclusion: Combination of low dose IV ketamine and IV parecoxib was more effective as pre-emptive analgesia compared to IV ketamine alone for post laparotomy patients who were on PCAM as post-operative analgesia.